2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487135
|View full text |Cite
|
Sign up to set email alerts
|

Learning optimal navigation actions for foresighted robot behavior during assistance tasks

Abstract: We present an approach to learn optimal navigation actions for assistance tasks in which the robot aims at efficiently reaching the final navigation goal of a human where service has to be provided. Always following the human at a close distance might hereby result in inefficient trajectories, since people regularly do not move on the shortest path to their destination (e.g., they move to grab the phone or make a note). Therefore, a service robot should infer the human's intended navigation goal and compute it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Methods like SARL [36] or MP-RGL [37] capture interactions between robot and humans with excellent results, but rely on the known velocity of humans. Others infer or forecast human behavior by predicting their longterm goals, or by predicting their future motion and activities [38], often by employing 3D lidar or RGB(D) cameras [39]- [43]. Wang et al [44] processed optical flow from RGB data as temporal information with an attention module to detect actions.…”
Section: B Learning-based Navigationmentioning
confidence: 99%
“…Methods like SARL [36] or MP-RGL [37] capture interactions between robot and humans with excellent results, but rely on the known velocity of humans. Others infer or forecast human behavior by predicting their longterm goals, or by predicting their future motion and activities [38], often by employing 3D lidar or RGB(D) cameras [39]- [43]. Wang et al [44] processed optical flow from RGB data as temporal information with an attention module to detect actions.…”
Section: B Learning-based Navigationmentioning
confidence: 99%
“…Some innovative attempts have been made to improve the intelligence and efficiency of the following robot, given knowledge of the target human's predicted movements. 19,20 For example, Bayoumi and Bennewitz predicted human motion using a modified Markov decision process (MDP) 21 and developed a DRL-based navigator, which resulted in foresighted following behaviors and shorter following trajectories. 19 Recovery mechanisms, based on human trajectory prediction, have also been implemented when the robot misses a target in dynamic environments.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 For example, Bayoumi and Bennewitz predicted human motion using a modified Markov decision process (MDP) 21 and developed a DRL-based navigator, which resulted in foresighted following behaviors and shorter following trajectories. 19 Recovery mechanisms, based on human trajectory prediction, have also been implemented when the robot misses a target in dynamic environments. 20 These studies suggested that the prediction of user movement could significantly improve following efficiency and the foresightedness of the robot, but the mechanisms how it contributes to following stability remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%